2020
DOI: 10.1088/1741-2552/abb63a
|View full text |Cite
|
Sign up to set email alerts
|

Acoustoelectric imaging of deep dipoles in a human head phantom for guiding treatment of epilepsy

Abstract: Objective. This study employs a human head model with real skull to demonstrate the feasibility of transcranial acoustoelectric brain imaging (tABI) as a new modality for electrical mapping of deep dipole sources during treatment of epilepsy with much better resolution and accuracy than conventional mapping methods. Approach. This technique exploits an interaction between a focused ultrasound (US) beam and tissue resistivity to localize current source densities as deep as 63 mm at high spatial resolution (1 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…This study achieved the first SSVEP measurement with millimeter spatial resolution in ABI live rats (Song et al, 2021 )). The results of phantom experiments and animal experiments demonstrate that ABI is able to localize simulated current sources or firing neurons at high resolution under a variety of conditions, demonstrating the feasibility of ABI for detecting intracranial neuronal firing (Barragan et al, 2020 ). In the next study, as a transition between mimic brain tissue phantom experiments and in vivo brain experiments, we can try to use live brain slices for bio-current source imaging in in vitro experiments, which is a must before its application in the clinic.…”
Section: Research Progressmentioning
confidence: 89%
See 1 more Smart Citation
“…This study achieved the first SSVEP measurement with millimeter spatial resolution in ABI live rats (Song et al, 2021 )). The results of phantom experiments and animal experiments demonstrate that ABI is able to localize simulated current sources or firing neurons at high resolution under a variety of conditions, demonstrating the feasibility of ABI for detecting intracranial neuronal firing (Barragan et al, 2020 ). In the next study, as a transition between mimic brain tissue phantom experiments and in vivo brain experiments, we can try to use live brain slices for bio-current source imaging in in vitro experiments, which is a must before its application in the clinic.…”
Section: Research Progressmentioning
confidence: 89%
“…Because the skull is a strong absorber and disperser of ultrasound and electrical signals (Zhang et al, 2021 ), in earlier studies, the skull cap was removed and ultrasound waves were delivered directly through the surface of the brain phantom (Qin et al, 2016 ). Barragan used a head phantom with a real human skull to demonstrate 4D ABI for mapping time-varying monopoles and dipoles at depths >60 mm with detection thresholds <0.5 mA ( Figure 4 ) (Barragan et al, 2020 ). In 2022, Zhang used FUS irradiation to simulate the dipole of neuronal firing, and the simulation and experimental results showed that the localization and decoding results were highly consistent with the predicted situation (Zhang et al, 2022 )).…”
Section: Research Progressmentioning
confidence: 99%
“…This further affirms the brain imaging capabilities of tABI. In previous studies, it has been shown that appropriately increasing the number of electrodes and choosing an appropriate electrode layout can significantly improve the signal-to-noise ratio of images [21] [25]. We will try adding electrode arrays to improve the imaging quality of tABI in future work.…”
Section: Discussionmentioning
confidence: 99%
“…Then, tABI was presented by Y. Qin et al in 2017 [6], which is like AENI but more specific in electromagnetic signal type. The feasibility of using an artificial current source for AEI in a human head model and rat hippocampus has been confirmed, and many studies have shown that tABI may be able to accurately resolve deep neuron currents with a high spatial resolution (<3mm) [17][18][19][20][21]. But these models mainly use artificial current sources to simulate neural activity and lack valuable real brain data for verification and optimization.…”
Section: Introductionmentioning
confidence: 97%
“…[2,[4][5][6] AE has been recently used to realize the acoustoelectric imaging (AEI) of biological tissue which has been successfully applied for breast cancer detection, [7] cardiac imaging, [8][9][10][11][12][13] and mapping deep brain stimulation (DBS) currents during transcranial brain imaging. [14][15][16][17][18][19] In parallel, in recent years low-density focused ultrasound (LIFU) has been studied as an alternative novel non-invasive brain stimulation technique. [20,21] It safely induces reversible AE in biological tissues and possesses dual advantages of exquisite spatial specificity and deep penetration.…”
Section: Introductionmentioning
confidence: 99%